Estrutura supramolecular de cristais multicomponentes derivados do ácido salicílico e do ibuprofeno - Tier, Aniele Zolin (2017)
This work presents the study of multicomponent crystals formed by salicylic acid (AS) with 1,2-Phenylenediamine (FEN) and 3-Amino-1,2-4-1H-triazole (TRIA) as amines; and rac-ibuprofen (IBU) with 3-amino-5-methyl-1H-pyrazole (PIR) and tyramine (TIR) as amines. Thus, four new multicomponent crystals were synthesized and characterized by differential scanning calorimetry, infrared spectroscopy, powder X-ray diffraction and single crystals X-ray diffraction. The main intermolecular interaction present in the supramolecular structure of the multicomponent crystals was the hydrogen bonding. This interaction promoted the crystallization of the multicomponent crystals from the formation of (i) a cyclic dimer, formed mainly by the interaction of the carboxylic acid group (AS or IBU) with the aromatic nitrogen and amine group that was characteristic of the multicomponent crystals of the acids with the substituted amino heterocycles (AS...TRIA and IBU...PIR); ii) tetramer formed by interactions of the carboxylic acid (AS or IBU) and amine which was characteristic of the multicomponent crystals of the acids with the primary amines 1,2-phenylenediamine and tyramine (AS...FEN and IBU...TIR). In the cases of dimer formation, the hydrogen bonds between the coformers were characteristic of heterosyntons, differentiating the supramolecular structure of the multicomponent crystals of their coformers and also of other multicomponent crystals already reported in the literature for the same coformers. The stability of the crystal lattice and the dimers and tetramers that governed the supramolecular arrangement of the multicomponent crystals and coformers was determined to evaluate the stability of the molecules in both systems. The results showed that the energy of the crystalline lattice is not the determining factor for the formation of the multicomponent crystal. On the other hand, the energy of the dimers and tetramers that initiated the growth of the crystal and added to it a greater contribution to stability, has been shown to be the factor that defines the growth of the monocomponent or multicomponent crystal. This fact becomes clear when we observe that the multicomponent crystals derived from AS formed more stable heterodimers than the homodimers of the coformers. The IBU-derived crystals formed more stable heterodimers than the homodimers present in the IBU polymorph II, and less stable than the polymorph I homodimer, showing that the crystallization of the IBU in these multicomponent systems occurs by the conversion of the polymorph I to the polymorph II and Then forms the multi-component crystal.